1993
DOI: 10.1177/10454411930040032401
|View full text |Cite
|
Sign up to set email alerts
|

Altered Responses to Agonists after Chronic In Vivo Atropine Administration in Rat Parotid Acini

Abstract: Salivary gland hypofunction, resulting from a variety of perturbations including prescribed medications, is associated with adverse effects on the health of the oral cavity. In the present study, we investigated the in vivo effects of chronic administration of atropine, a muscarinic antagonist, on the acute response of rat parotid acini to a-adrenergic and muscarinic stimulation. The regulation of intracellular pH (pHj) and cytosolic free Ca2+ ([Ca2+]i) were monitored using dual wavelength microfluorometry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…In freshly isolated SMG acinar cells, α 1 ‐receptors may not play a critical role in regulating the Ca 2+ signal. It has been reported that parotid gland (PG) acinar cells respond strongly to α 1 ‐agonists, manifesting large increases in IP 3 formation and Ca 2+ mobilization (32, 33), although Soltoff etal . (34) observed that stimulation of rat PG acinar cells with 10 μ M phenylephrine only slightly (35%) increased [Ca 2+ ] i .…”
Section: Discussionmentioning
confidence: 99%
“…In freshly isolated SMG acinar cells, α 1 ‐receptors may not play a critical role in regulating the Ca 2+ signal. It has been reported that parotid gland (PG) acinar cells respond strongly to α 1 ‐agonists, manifesting large increases in IP 3 formation and Ca 2+ mobilization (32, 33), although Soltoff etal . (34) observed that stimulation of rat PG acinar cells with 10 μ M phenylephrine only slightly (35%) increased [Ca 2+ ] i .…”
Section: Discussionmentioning
confidence: 99%